Antigenic and immunological determinants of acute allergic susceptibility to meat in a uniquely defined cohort in the Eastern Cape - Murangi, Tatenda (Department of Pathology, 2024)
Allergic sensitization can occur after allergen exposure through the oral-mucosal or cutaneous route. Allergic remission is associated with a decrease in total and specific IgE levels to allergens. Ascaris lumbricoides is a potent inducer of IgE through the establishment of a strong Th2 environment. IgE induction following A. lumbricoides infection is a risk for allergic sensitization. Tick disruption of host skin during feeding has a systemic effect resulting in the induction of a Th2 phenotype with elevated IgE production. Raised IgE can be driven by exposure to parasite proteins and lipids with complex glycosylation patterns. Our study demonstrates the presence of alpha-gal in both adult and larval developmental stages of A. lumbricoides, Amblyomma hebraeum and Rhipicephalus evertsi. Alpha-gal glycosylation was prominent on 100kDa and 130-250kDa protein bands. A. hebraeum and R. evertsi showed differential expression of alpha-gal glycosylated proteins during feeding with band intensity increasing proportionally to an increase in feeding time in the salivary glands. Immunolocalization of alpha-gal in A. lumbricoides adult worms showed staining in the lining of the gastrointestinal tract while in A. hebraeum and R. evertsi, staining was prominent in the salivary glands. Screening for IgE demonstrated elevated IgE to A. lumbricoides in human research participants with challenge-proven alpha-gal allergy which positively correlated to alpha-gal IgE. Furthermore, non-alpha gal glycosylated A. lumbricoides antigens caused significant activation of a humanized rat basophil RS-ATL8 IgE reporter cell system after incubation with sera from alpha-gal allergic individuals. Interestingly, serum IgG4 from alphagal allergic individuals showed surface labelling of A. lumbricoides larvae invitro. Alpha-gal positive participants also demonstrated raised IgE and IgG4 towards A. hebraeum proteins. Proteomic analysis suggests alpha-gal glycosylation to be present on alpha-2-macroglobulin found in lysates from both A. lumbricoides and A. hebraeum. These findings present A. lumbricoides, A. hebraeum and R. evertsi as potential sources of sensitization to alpha-gal and hypersensitivity reactions including anaphylaxis in humans after the consumption of red meat or use of pharmaceutical products from a mammalian source